Processing methods for multichannel radiometric data with application to atmospheric radon - Clifton, Roger L. (Curtin University, 1989)
Airborne multichannel radiometric data are collected for lithology mapping. Established processing methods efficiently extract the potassium and thorium distributions, but confuse the uranium in the ground with the radon gas it releases into the atmosphere. This thesis uses the multichannel character to help separate the true uranium signal from the radon effects. The processing is reviewed and some methods for reducing the effects of radon are examined.